The Effect of Social Interaction and Internet Utilization on Students’ Self-Regulated Learning - Sudwiarrum, Diaz Ayu; Setyowati, Dewi Liesnoor; Husain, Fadly (JESS (Journal of Educational Social Studies), 2023)
This study aims to analyze students' social interactions, internet use, self-regulated learning, and the influence of social interaction and internet use on self-regulated learning of students at SMP Islam Al-Azhar 5 Cirebon. This research is a quantitative study with a population of 180 students of class VIII SMP Islam Al-Azhar 5 Cirebon which were chosen using random sampling In this study, questionnaires and documentation were used to collect data. Multiple linear regression was employed in the data analysis approach. According to the findings of this study: (1) the level of students’ social interaction of 62% belongs to the fairly good category, (2) the level of student’s internet utilization by 59% belongs to the fairly good category, (3) the pearson correlations product moment value of social interaction and internet utilization on students’ self-regulated learning of 0.735 has a strong or high correlation, meaning "There is a significant effect of social interaction and internet use on self-regulated learning of students of SMP Islam Al-Azhar 5 Cirebon". The magnitude of the effect based on the analysis of the coefficient of determination is 53.2% while the remaining 46.8% is influenced by other variables not included in the research model.